What helps the helpers? Resilience and risk factors for general and profession-specific mental health problems in psychotherapists during the COVID-19 pandemic - Zerban, Matthias; Puhlmann, Lara Marie Christine; Lassri, Dana; Fonagy, Peter; Montague, P. Read; Kiselnikova, Natalia; Lorenzini, Nicolas; Desatnik, Alex; Kalisch, Raffael; Nolte, Tobias (Frontiers in Psychology, 2023)
Introduction: Although the COVID-19 pandemic has severely affected wellbeing of at-risk groups, most research on resilience employed convenience samples. We investigated psychosocial resilience and risk factors (RFs) for the wellbeing of psychotherapists and other mental health practitioners, an under-researched population that provides essential support for other at-risk groups and was uniquely burdened by the pandemic. Method: We examined 18 psychosocial factors for their association with resilience, of which four were chosen due to their likely relevance specifically for therapists, in a cross-sectional multi-national sample (N=569) surveyed between June and September 2020. Resilience was operationalized dimensionally and outcome-based as lower stressor reactivity (SR), meaning fewer mental health problems than predicted given a participant's levels of stressor exposure. General SR (SRG) scores expressed reactivity in terms of general internalizing problems, while profession-specific SR (SRS) scores expressed reactivity in terms of burnout and secondary trauma, typical problems of mental health practitioners. Results: Factors previously identified as RFs in other populations, including perceived social support, optimism and self-compassion, were almost all significant in the study population (SRG: 18/18 RFs, absolute βs=.16-.40; SRS: 15/18 RFs, absolute βs=.19-.39 all Ps <.001). Compassion satisfaction emerged as uniquely relevant for mental health practitioners in regularized regression. Discussion: Our work identifies psychosocial RFs for mental health practitioners' wellbeing during crisis. Most identified factors are general, in that they are associated with resilience to a wider range of mental health problems, and global, in that they have also been observed in other populations and stressor constellations.